EFL Students’ Perception Toward The Use Of E-learning Platform as an Effective Tool - Mubarok, Harir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
An online class is a form of learning media that uses the internet, especially during the COVID-19 pandemic. E-learning is a platform that utilizes information and communication technology to facilitate learning, whether traditional, online, or hybrid, through the application of digital technology. This study examines the perceptions of English Education Department students at the State Islamic University of Maulana Malik Ibrahim Malang regarding the use of the E-learning platform developed by the State Islamic University of Maulana Malik Ibrahim Malang in the IT for ELT course. The number of respondents in this study was 21 students of English Education at the State Islamic University of Maulana Malik Ibrahim Malang who were taking IT for ELT courses in the sixth semester. Meanwhile, this study uses a qualitative method that focuses on case studies. The results of this study indicate that students majoring in English education have a positive perception of the E-learning platform at the State Islamic University Maulana Malik Ibrahim Malang as a learning tool in the IT for ELT course.